The lost continent : travels in small town America - Bryson, Bill, 1951- (Black Swan, 1999)
And, as soon as Bill Bryson was old enough, he left. Des Moines couldn’t hold him, but it did lure him back. After ten years in England, he returned to the land of his youth, and drove almost 14,000 miles in search of a mythical small town called Amalgam, the kind of trim and sunny place where the films of his youth were set. Instead, his search led him to Anywhere, USA; a lookalike strip of gas stations, motels and hamburger outlets populated by lookalike people with a penchant for synthetic fibres. He discovered a continent that was doubly lost; lost to itself because blighted by greed, pollution, mobile homes and television; lost to him because he had become a stranger in his own land.